INVENTORY OF ARCHITECTURAL HERITAGE SHOPHOUSES IN JALAN MENDALING, KAJANG OLD TOWN - Mohamed, Amir Ridhwan; Asif, Nayeem; Abdullah, Fadzidah; Yusof, Zeenat Begam; Azmin, Aida Kesuma (Journal of Architecture, Planning and Construction Management, 2023)
This study sheds light on the current condition of heritage shophouses in Jalan Mendaling, Kajang, underscoring the urgency of their preservation. By recognizing these structures’ architectural value and historical significance, it is hoped that appropriate measures will be taken to conserve and protect Kajang’s unique heritage for future generations. Located in the southeastern part of Selangor, Malaysia, Kajang stands as one of the oldest towns in the region, with a rich historical background. Formerly a bustling trading center and tin mining area, Kajang now holds significant cultural heritage through its assortment of shophouses, reflecting the town’s past architectural styles. These shophouses, constructed in various designs, including Early Shophouse, Eclectic Shophouse, and Neoclassical, play a pivotal role in shaping Kajang’s distinctive identity. This research aims to assess the existing state and architectural characteristics of heritage shophouses in Jalan Mendaling, Kajang. Through observation, the study highlights the pressing need for preservation and intervention by relevant authorities to safeguard these invaluable structures. Regrettably, many shophouses have undergone renovations that compromise authenticity, demanding immediate attention to ensure long-term conservation. Nevertheless, the research successfully identified seven shophouses that have remarkably maintained their original façades, thus retaining their historical significance and architectural allure. Data collection for this research involved the utilization of a comprehensive checklist. Initial observations revealed a total of 42 shop lots on Jalan Mendaling, Kajang, out of which only 39 retained their structures. Consequently, the final phase of observation concentrated on a select group of seven shop lots that preserved the original façades and architectural elements, signifying the true essence of heritage without substantial alterations influenced by modern practices. The findings of this research possess significant implications for raising awareness regarding the importance of conserving and preserving heritage shophouses. Furthermore, the outcomes can be utilized to formulate comprehensive guidelines tailored explicitly for the conservation and preservation of heritage shophouses in Kajang, ensuring the sustainable safeguarding of these cultural treasures.